The changing of the guard : planning for succession at Madison Childrens Foundation (A) - Howard, Liz Livingston, (SAGE Knowledge. Cases., 2017)
In mid-2008, David Miller, the CEO of the Madison Childrens Foundation (MCF), is beginning to contemplate the future of the organization. As the founding CEO, Miller has been the face of MCF since its inception in 1993. The foundation has a strong track record of success and has established a reputation as a change maker and partner in the community, having made grants of more than $60 million to local organizations. Although its grant-making has increased, MCFs staff has not grown over time. The board has changed composition over the past six years, adding more community residents and working board members. The board succession plan is fairly well organized, with a nominating committee and a good understanding of skill sets needed and the expectations for board members. However, there is no CEO succession plan. Board members have been raising the question in a non-confrontational manner for the past two or three years, and now Miller believes the time has come to create a CEO succession strategy for MCF. The critical questions raised by this case include: What roles do/should CEOs and boards play in initiating and implementing a leadership succession process? How does the implementation of a leadership succession process affect the senior staff at an organization? How should external stakeholders be engaged in the leadership succession process?